Influence of Aging Temperature During Artificial Aging Process on Aluminium Alloy to the Mechanical Properties - Atria Pradityana; Budi Luwar Sanyoto; Erik Kurniawan Widyantoro (IPTEK Journal of Proceedings Series, 2019)
The aging process is a hardening process that aims to change the physical properties and mechanical properties of the material according to needs. This process is carried out by holding the heating process at a certain temperature for a certain period of time. Aluminium alloys have good mechanical properties. One way to improve the mechanical properties of a material is by hardening process. This aging process is one example of the hardening process. In this study, an artificial aging process was carried out on aluminium 6061 alloys. Analysis was carried out on the effect of aging temperature during the artificial aging process. Temperature variations used are 100, 125, 150, 175, 200oC. The holding time is 1 hour. At the beginning of the process, heating with a heat treatment solution was carried out at 300oC for 1 hour. Then quenching with water media. The next work process, heat treatment is carried out with the variations mentioned above. The last step is to do quenching again. Analysis of the mechanism is carried out on impact strength, hardness value and microstructure. The results of the analysis show that the best aging temperature range during the artificial aging process in 6061 aluminium alloys is at 150 to 200oC. In this study, the best impact strength was produced at an aging temperature of 200° C, the best hardness value at an aging temperature of 150° C and a microstructure that contained the least precipitations at a temperature of 200°C.